Experimental investigation of enhancement heat dissipation in a novel heat sink under simultaneous impact of impingement jet and magnetic field - Azadi, Shervin; Abjadi, Ali; Vahdat Azad, Abazar; Ahmadi Danesh Ashtiani, Hossein; Afshar, Hossein (Frontiers in Mechanical Engineering, 2024)
In today’s world, research on cooling systems that can effectively reduce the cooling time of heat sinks and enhance heat transfer efficiency in a shorter duration is extremely crucial. This experimental study analyzed the cooling time by simultaneously utilizing two cooling techniques. This involved the passage of ferrofluid (Fe3O4/water) through three channels of a heat sink under the influence of a magnetic field, as well as the application of an air impingement jet on the heat sink’s surface. A novel plate-fin heat sink with dimensions of 40 mm (L) × 31.32 mm (W) × 23.5 mm (H) consists of three channels with a diameter of 3 mm for crossing ferrofluid flow and 24 channels on the top of the heat sink for crossing the air was designed and built for the study. The heat sink was exposed to an air impingement jet and an external magnetic field simultaneously. Multiple tests were conducted to determine the convective heat transfer coefficients of the heat sink over time under specific conditions, including a magnetic field of 800 G, a volume fraction of 3%, a Reynolds number of 600 for the ferrofluid, and a mass flow rate of 0.1 kg/s. It was discovered that using the combined method of magnetic field and impingement jet (MF-IJ) compared to cooling by air impingement jet with the simultaneous passage of pure water through the ferrofluid channels (Water-IJ), as well as the ferrofluid flow under a magnetic field without the impingement jet (MF) methods for the designed heat sink, can increase the maximum heat transfer coefficient by 27.4% and 46.4%, respectively. The findings of this study suggest that using the MF-IJ cooling method as a flow control mechanism, along with this innovative geometry, can reduce the cooling time of the heat sinks.